Deliberative Policy Analysis of Green Open Spaces in Lebak Regency Banten Province - Harits Hijrah Wicaksana (Journal of Governance, 2024)
Increasing population growth in an urban area is the main factor in reducing space utilization. One of them is green open space. In response to this, the Regional Government of Lebak Regency issued a policy in the form of Regional Regulation Number 2 of 2011 concerning Green Open Space in the Urban Area of the Capital City of Lebak Regency. Researchers are interested in analyzing the policy planning process for the provision and use of green open space in the urban area of Lebak Regency from a deliberative perspective. The research results showed that population density resulted in the emergence of slum areas and low-income communities. Apart from that, the lack of public awareness of clean and healthy living behaviors is one of the contributing factors. Plans to provide and utilize green open space in the urban area of Lebak Regency have been hampered due to construction and development in the economic sector. Moreover, the importance and need for green open space to overcome disaster-prone areas such as landslide-prone and inundation-prone areas need to be resolved by the Lebak Regency Regional Government. Based on these conditions, it is necessary to create a resolution or development policy that can resolve two factors, namely economic development and the fulfillment of green open space. Therefore, one solution that can be provided is the Green City Development Program.